Intense biogeochemical iron cycling revealed in Neoarchean micropyrites from stromatolites. (1st November 2021) - Decraene, Marie-Noëlle; Marin-Carbonne, Johanna; Thomazo, Christophe; Olivier, Nicolas; Philippot, Pascal; Strauss, Harald; Deloule, Etienne
Abstract: Iron isotope compositions of sedimentary pyrites (FeS2 ) are used to constrain the redox evolution of the Precambrian ocean and early Fe-based metabolisms such as Dissimilatory Iron Reduction (DIR). Sedimentary pyrites can record biotic and abiotic iron reduction, which have similar ranges of Fe isotopic fractionation, as well as post-depositional histories and metamorphic overprints that can modify Fe isotope compositions. However, some exceptionally well-preserved sedimentary records, such as the stromatolite-bearing Tumbiana Formation (ca. 2.7 Ga, Western Australia) have been proven to retain primary information on Early Neoarchean microbial ecosystems and associated metabolic pathways. Here, we present in situ Fe isotope measurements of micropyrites included in four stromatolites from the Tumbiana Formation in order to assess iron respiration metabolism using Fe isotope signatures. A set of 142 micropyrites has been analyzed in three lamina types, i.e . micritic, organic-rich and fenestral laminae, by Secondary Ion Mass Spectrometry (SIMS), using a Hyperion radio-frequency plasma source. The diversity of laminae is attributed to specific depositional environments, leading to the formation of Type 1 (micritic laminae) and Type 2 (organic-rich laminae) and early diagenetic effects (Type 3, fenestral laminae). Type 1 and 2 laminae preserved comparable δ 56 Fe ranges, respectively from −1.76‰ to +4.15‰ and from −1.54‰ to +4.44‰. Type 3 laminae recorded a similar range, although slightly more negative δ 56 Fe values between −2.20‰ and +2.65‰. Globally, our data show a large range of δ 56 Fe values, from −2.20‰ to +4.44‰, with a unimodal distribution that differs from the bimodal distribution previously reported in the Tumbiana stromatolites. Such a large range and unimodal distribution cannot be explained by a unique process ( e.g ., biotic/abiotic Fe reduction or pyrite formation only controlled by the precipitation rate). It rather could reflect a two-step iron cycling process in the sediment pore water including i) partial Fe oxidation forming Fe(OH)3 with positive δ 56 Fe values followed by ii) partial, possibly microbially induced, Fe reduction leading to Fe 2+ availability for pyrite formation by sulfate reducers carrying both negative δ 56 Fe and δ 34 S signatures. In this model, the buildup and subsequent reduction through time of a residual Fe(OH)3 reservoir arising from the activity of methanotrophs, can explain the strongly positive δ 56 FeFe(OH)3 values up to 4‰. These results indicate that Archean microbial mats have been the site of the interaction of several closely linked biogeochemical cycles involving Fe, S and C.